Philology and criticism a guide to Mahabharata textual criticism - Adluri, Vishwa; Bagchee, Joydeep (Cultural, historical, and textual studies of South Asian religions, 2018)
Philology and Criticism contrasts the Mahābhārata’s preservation and transmission within the Indian scribal and commentarial traditions with Sanskrit philology after 1900, as German Indologists proposed a critical edition of the Mahābhārata to validate their racial and nationalist views. Vishwa Adluri and Joydeep Bagchee show how, in contrast to the Indologists’ unscientific theories, V. S. Sukthankar assimilated the principles of neo-Lachmannian textual criticism to defend the transmitted text and its traditional reception as a work of law, philosophy and salvation. The authors demonstrate why, after the edition’s completion, no justification exists for claiming that an earlier heroic epic existed, that the Brahmans redacted the heroic epic to produce the Mahābhārata or that they interpolated "sectarian" gods such as Vis.n.u and Śiva into the work. By demonstrating how the Indologists committed technical errors, cited flawed and biased scholarship and used circular argumentation to validate their racist and anti-Semitic theories, Philology and Criticism frees readers to approach the Mahābhārata as "the principal monument of bhakti" (Madeleine Biardeau). The authoritative guide to the critical edition’s correct use and interpretation, Philology and Criticism urges South Asianists to view Hinduism as a complex debate about ontology and ethics rather than through the lenses of "Brahmanism" and "sectarianism." It launches a new world philology—one that is plural and self-reflexive rather than Eurocentric and ahistorical